Reduced mortality rate in patients with severe traumatic brain injury treated with brain tissue oxygen monitoring - Stiefel, Michael F; Spiotta, Alejandro; Gracias, Vincent H; Garuffe, Alicia M; Guillamondegui, Oscar; Maloney-Wilensky, Eileen; Bloom, Stephanie; Grady, M Sean; LeRoux, Peter D (Journal of neurosurgery, 2005)
An intracranial pressure (ICP) monitor, from which cerebral perfusion pressure (CPP) is estimated, is recommended in the care of severe traumatic brain injury (TBI). Nevertheless, optimal ICP and CPP management may not always prevent cerebral ischemia, which adversely influences patient outcome. The authors therefore determined whether the addition of a brain tissue oxygen tension (PO2) monitor in the treatment of TBI was associated with an improved patient outcome. Patients with severe TBI (Glasgow Coma Scale [GCS] score < 8) who had been admitted to a Level I trauma center were evaluated as part of a prospective observational database. Patients treated with ICP and brain tissue PO2 monitoring were compared with historical controls matched for age, pathological features, admission GCS score, and Injury Severity Score who had undergone ICP monitoring alone. Therapy in both patient groups was aimed at maintaining an ICP less than 20 mm Hg and a CPP greater than 60 mm Hg. Among patients whose brain tissue PO2 was monitored, oxygenation was maintained at levels greater than 25 mm Hg. Twenty-five patients with a mean age of 44 +/- 14 years were treated using an ICP monitor alone. Twenty-eight patients with a mean age of 38 +/- 18 years underwent brain tissue PO2-directed care. The mean daily ICP and CPP levels were similar in each group. The mortality rate in patients treated using conventional ICP and CPP management was 44%. Patients who also underwent brain tissue PO2 monitoring had a significantly reduced mortality rate of 25% (p < 0.05). The use of both ICP and brain tissue PO2 monitors and therapy directed at brain tissue PO2 is associated with reduced patient death following severe TBI.